Surat Panggul: Prenuptial Agreement In The Dayak Ngaju Tribe - Nissa, Jamilatun; Huda, Miftahul (Sakina: Journal of Family Studies, 2024)
The traditional marriage of the Ngaju Dayak tribe is a mandatory ritual for the local community to uphold ancestral customs and cultural values. The marriage ritual of the Ngaju Dayak community is formed from several parts that have been patterned in one unit, It aims to meaning of the marriage ceremony in the aspects of custom and religion. One of the traditional marriage procedures of the Ngaju Dayak Tribe is a Surat Panggul or premarital agreement agreed perpetuating the marriage so that divorce does not occur. This is an interesting problem to be researched where the contents of the Surat Panggul or prenuptial agreement of the Ngaju Dayak tribe are contradictory or in harmony when viewed from Marriage Law No. 1 of 1974. This research is a juridical-empirical research using a qualitative descriptive approach. The result of this study is that the practice of the Dayak Ngaju community procession before marriage has benefits if carried out and does not conflict with the Qur'an hadith, can be classified as a custom that has a good impact and mashlahah.Then from the point of view of the provisions of the prenuptial agreement in Indonesia, namely those contained in Law No. 1 of 1974 concerning Marriage, surat panggul or this customary prenuptial agreement does not conflict with existing provisions.